Co je nového v doporučeních ESC 2021 pro kardiovaskulární prevenci? - Obrová, Jana; Jadrníčková, Pavla; Václavík, Jan (Vnitrni lekarstvi, 2022)
2021 ESC Guidelines on cardiovascular disease prevention in clinical practice provides a comprehensive view on preventive cardiology. It presents strategies to reduce the burden of atherosclerotic cardiovascular disease (CVD), both at the individual level and at the population level. Healthy lifestyle and aggressive control of cardiovascular risk factors remain the cornerstone of prevention. Classification of individuals into risk groups based on their clinical characteristics followed by a stepwise treatment-intensification is a novel recommended approach. Updated risk charts - SCORE2 and SCORE2-OP - are intended for estimation of 10-year fatal and non-fatal CVD risk in apparently healthy individuals. Targets and goals for LDL cholesterol, blood pressure, and glycaemic control remain as recommended in recent ESC Guidelines.
Keywords: kardiologie; Humans; Atherosclerosis; kardiovaskulární nemoci; healthy lifestyle; prevention; Cardiovascular Diseases; Risk Factors; atherosclerotic cardiovascular disease; treatment; cardiovascular risk factors; Hydroxymethylglutaryl-CoA Reductase Inhibitors; doppler ultrasound of uterine artery; statiny; rizikové faktory; SCORE2 and SCORE2-OP; Cardiology; LDL-cholesterol; lidé; ateroskleróza; Cholesterol, LDL